Intensitas Latihan Fisik Ringan-Berat Kurang Memengaruhi Kadar Follicle Stimulating Hormone Serum Mencit Betina - Wijayanti, Anggis Putri; Herawati, Lilik; Frety, Endyka Erye; Faizah, Zakiyatul (Jurnal Veteriner, 2022)
Physical exercise can cause a change in hormonal system resulting an irregularities of menstrual cycle.  Menstrual irregularities is one of the ovulation disruption symptoms.  The most important cause of ovulation disruption is a decrease of Gonadothropin Releasing Hormone (GnRH) which is regulated by hipothalamus-pitutary-ovarium axis (HPO axis) mechanism resulting in decreased of Follicle Stimulating Hormone (FSH) secretion. HPO axis mechanism disruption can be caused by severe physical activity. Methods: This research took place in phaculty of veterinary of Airlangga University.  The methods of this research was experimental laboratory study with Randomized Post-test Only Control Group Design. The number of sample were 28 female mice divided into four groups with a sampling technique using probability sampling with the type of simple random sampling. The independent variable of this research were moderate and severe physical exercise. The dependent variable were serum Follicle Stimulating Hormone (FSH) levels. The data were analyzed using SPSS 25 software with one way- ANOVA test. This research was conducted to analyze the difference effect of low to severe physical exercise on serum Follicle Stimulating Hormone (FSH) levels in female mice. The result is there were no significant difference in levels of Follicle Stimulating Hormone (FSH) mice with low, moderate and severe physical activity. The conclusion that can be taken in this research is there is no difference in the effect of low, moderate to severe physical exercise on serum Follicle Stimulating Hormone levels in female mice.